Clinical implications of the Women’s Ischemia Syndrome Evaluation : interrelationships between symptoms, psychosocial factors and cardiovascular outcomes - Handberg, Eileen M. (2013)
Cardiovascular disease (CVD) remains the leading cause of death in the US and is associated with several modifiable (hypertension, diabetes, high cholesterol, tobacco use, physical inactivity, obesity and unhealthy diet) and nonmodifiable (age, gender, family history) risk factors. The role of psychosocial risk factors in the development of CVD has a growing body of literature, and differences in men and women have been identified. The Women’s Ischemia Syndrome Evaluation (WISE) provides insight into psychosocial risk factors in a cohort of women presenting with chest pain who had a comprehensive battery of psychosocial assessments and who had long-term follow up. This review focuses on symptom presentation for chest pain, and its relationship to CVD morbidity and mortality, quality of life, healthcare costs, and psychosocial predictor variables including anxiety, depression, hostility, and social networks. In WISE, persistent chest pain was associated with increased rate of adverse events and relatively high rates of depression and anxiety with reduced functional capacity and impaired QOL over a median of 6 years follow-up. More research is needed to better understand these relationships between symptoms and negative emotions and determine if psychological (pharmacologic and/or cognitive) interventions might impact both psychological and cardiovascular outcomes.